A network medicine approach to study comorbidities in heart failure with preserved ejection fraction - Lanzer, Jan David; Valdeolivas, Alberto; Pepin, Mark; Hund, Hauke; Backs, Johannes; Frey, Norbert; Friederich, Hans-Christoph; Schultz, Jobst-Hendrik; Sáez Rodríguez, Julio; Levinson, Rebecca T. (BMC medicine, 2023)
Comorbidities are expected to impact the pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF). However, comorbidity profiles are usually reduced to a few comorbid disorders. Systems medicine approaches can model phenome-wide comorbidity profiles to improve our understanding of HFpEF and infer associated genetic profiles.